CLINICAL, MAMMOGRAPHIC AND HISTOPATHOLOGICAL CORRELATION OF BREAST CANCER IN WOMEN AGED BETWEEN 50 AND 70 YEARS - Alvares, Beatriz Regina; Vieira, Mariana Meira; Almeida, Orlando José de; Jales, Rodrigo Menezes (Mastology, 2017)
Objective: To correlate the clinical, mammographic and histopathological findings of women aged between 50 and 70 years old who were diagnosed with breast cancer and were assisted between 1998 and 2013 at the Mastology Outpatient Clinic of the Center for Full Attention to Women’s Health in Universidade Estadual de Campinas (CAISM-Unicamp). Methods: This was a cross-sectional and retrospective study, in which the medical records and mammograms of 160 women were analyzed, a sufficient sample size for the statistical analysis. The variables used for comparison were the clinical, mammographic and histopathological findings, analyzed through descriptive and associative statistics. Results: O f t he 160 c ases a nalyzed, 76.9% w ere s ymptomatic, a nd t he m ain c linical fi ndings included palpable nodule (68.1%) and skin alterations (30%). The prevalent mammographic presentations in asymptomatic women were microcalcifications (48.7%), nodules (43.2%) and architectural distortion (8.1%). Regarding the histological type, 81.3% presented invasive ductal carcinoma (IDC) and 10.7%, ductal carcinoma in situ (DCIS). Conclusion: The present study showed that there was a predominance of symptomatic women with mammographic presentation of spiculated nodules and histological type of IDC. In the other patients with lesions detected in the screening test, pleomorphic microcalcifications were prevalent as the main finding of DCIS. Diagnostic mammography was the main form of detection of breast cancer, which may represent the lack of access of these women to screening or early detection of malignant lesions. This reveals the need to improve control actions and care protocols of these patients.